Studies on the potential link between antidepressant effect of Xiaoyao San and its pharmacological activity of hepatoprotection based on multi-platform metabolomics. (1st March 2020) - Chen, Congcong; Yin, Qicai; Tian, Junshen; Gao, Xiaoxia; Qin, Xuemei; Du, Guanhua; Zhou, Yuzhi
Abstract: Ethnopharmacological relevance: In traditional Chinese medicine (TCM) theory, depression is considered to be "liver qi stagnation", and relieving "liver qi stagnation" is regarded as an effective method for treating depression. Xiaoyao San (XYS) is a well-known TCM formula for the treatment of depression by relieving "liver qi stagnation". This formula consists of Radix Paeoniae Alba ( Paeonia lactiflora Pall.), Radix Bupleuri ( Bupleurum chinense DC.), Poria ( Poria cocos (Schw.) Wolf), Rhizoma Atractylodis Macrocephalae ( Atractylodes macrocephala Koidz.), Radix Angelicae Sinensis ( Angelica sinensis (Oliv.) Diels), Radix Glycyrrhizae ( Glycyrrhiza uralensis Fisch.), Rhizoma Zingiberis Recens ( Zingiber officinale Roscoe) and Herba Menthae Haplocalycis ( Mentha haplocalyx Briq.). Aim of the study: Several studies have suggested that depression is associated with liver injury. XYS was a well-known TCM formula for the treatment of depression and liver stagnancy. However, it was still unknown whether the antidepressant effect of XYS is related to the pharmacological activity of hepatoprotection. The aim of this study was to elucidate the potential link between the antidepressant and hepatoprotective effect of XYS. Materials and methods: A depression rat model was established by the CUMS (chronic unpredictable mild stress) procedure. The antidepressant effect of XYS was assessed by the behavioral indicators, and the hepatoprotective effect of XYS was evaluated through biochemical assays. 1 H-NMR and LC/MS-based liver metabolomics were performed to discover key metabolic pathways involved in the antidepressant and hepatoprotective effects of XYS. Further, the key pathway was validated using commercial kits. Results: The results demonstrated that XYS pretreatment could significantly improve the depressive symptom induced by CUMS. More importantly, the results demonstrated that liver injury was observed in the CUMS model rats, and XYS had a hepatoprotective effect by reducing the activities of AST and ALT in serum, increasing the levels of SOD and GSH-Px and reducing the contents of MDA, IL-6, and IL-1β in the liver. In addition, the NMR and LC/MS-based metabolomics results indicated that XYS improved 23 of the 35 perturbed potential liver biomarkers that were induced by CUMS. Among them, 9 biomarkers were significantly correlated with both depression and liver pathology, according to Pearson correlation analysis. Metabolic pathway analyses of these 9 biomarkers showed that glutamine and glutamate metabolism were the most important metabolic pathways. Furthermore, to verify glutamine and glutamate metabolism, the levels of glutamine and glutamate, and the activity of glutamine synthetase (GS) and glutaminase (GLS) were quantitatively determined in the liver by commercial kits, and these results were consistent with the metabolomics results. Conclusions: XYS could significantly improve the depressive and liver injury symptoms induced by CUMS. The metabolomics results indicate that the regulation of glutamine and glutamate metabolism to maintain the balance of ammonia and promote energy metabolism is a potential junction between the antidepressant and hepatoprotective effects of XYS. Graphical abstract: Image 1 Highlights: Metabolomic analysis of liver tissue based on 1 H-NMR and LC/MS. Elucidation of the potential link between XYS antidepressant effects and its hepatoprotection by metabolomics. Correlation analysis to discover a highly linearly related key metabolite between XYS antidepressant and hepatoprotection. Metabolomics results indicated that regulation of glutamine and glutamate metabolism was a potential junction. Regulation of glutamine and glutamate metabolism was a junction between antidepressant and hepatoprotective effect of XYS